2019
DOI: 10.1016/j.neuron.2019.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Micro-Macro Disconnect to Address Core Features of Seizure Networks

Abstract: Current drug treatments for epilepsy attempt to broadly restrict excitability to mask a symptom, seizures, with little regard for the heterogeneous mechanisms that underlie disease manifestation across individuals. Here, we discuss the need for a more complete view of epilepsy, outlining how key features at the cellular and microcircuit level can significantly impact disease mechanisms that are not captured by the most common methodology to study epilepsy, electroencephalography (EEG). We highlight how major a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 152 publications
1
66
0
Order By: Relevance
“…However, phar- Epileptogenesis is now considered as a circuit-level syndrome pathologically characterized by "excitation-inhibition" imbalance, caused by neuronal loss, synaptic reorganization and circuit rewiring. [38][39][40] Specially, long-term potentiation in glutamatergic transmission plays an important role in epileptogenesis. 41 We , and CaMKIIa-hM4Di mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, phar- Epileptogenesis is now considered as a circuit-level syndrome pathologically characterized by "excitation-inhibition" imbalance, caused by neuronal loss, synaptic reorganization and circuit rewiring. [38][39][40] Specially, long-term potentiation in glutamatergic transmission plays an important role in epileptogenesis. 41 We , and CaMKIIa-hM4Di mice, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that molecular dysfunction of these channel variants is relatively well-modeled and correctable in heterologous systems, translating these findings to therapies has faced unexpected challenges, likely due to the developmental, cellular, and synaptic complexity of the brain. Progress in tracing the critical steps between ion channel biophysics and pathological synchronization of cortical neurons thus requires precision genetic disease models and multi-level interrogations of their effects (Oyrer et al, 2018, Farrell et al, 2019. To address this, we created a mouse model with a missense mutation in a Na + -activated K + channel gene orthologous to a human missense mutation that causes an early-onset seizure disorder (ADNFLE) and has been shown in heterologous systems to be a GOF variant.…”
Section: Discussionmentioning
confidence: 99%
“…been a longstanding open question in the study of TLE (Farrell et al, 2019). Previous imaging and electrophysiological work examining the role of specific cell types in epileptic pathology has shown that inhibitory circuits play a critical role in shaping interictal dynamics in CA1 (Ewell et al, 2015, Muldoon et al, 2015, Miri et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Identification and characterization of circuit-level functional organization represents a critical step toward a general framework for resolving the micro-macro disconnect in chronic epilepsies (Farrell et al, 2019). Here we provide the first in vivo characterization of single cell and microcircuit-level dynamics in multiple cell populations in the epileptic DG and relate them to macroscale events in simultaneously recorded LFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation